THE EFFECTS OF CAPITAL, PROFITABILITY, LIQUIDITY UPON THE PREDICTION OF NATIONAL BANK FRAGILITY - SYARIEF GERALD PRASETYA (The Accounting Journal of Binaniaga, 2017)
An indication of banking crises within 2014 has been identified due to a slowing down of credit development, inappropriate resources, high cost of the funds and an increasing of NPL which have created a pressure on the banking profitability level which is a small value of net profit ratio upon the assets (ROA). Less profit has happened due to a decreasing of new credit distribution as well as an increasing of provision cost refers to credit problem (NPL). Banking sector is quite fragile, it is the result of banking network system either national or international. Early detection upon bank fragility can minize a jeopardy risk of banking sector systematically which is an improper intermediary function of banking. The research aims to discover whether a significant effect of capital, profitability and liquidity has happened upon the prediction of banking crises. Research method has applied associated descriptive and the analysis has applied logistics regression. Result of the research has identified that only probability variable has affected significantly the crises of banking, it is suggested that the banks should have to be more concerned about internal and external factors to improve bank profitability.Keywords : bank sector fragility, capita adequacy ratio, return on assets, non performing loan.